Assessing the multifunctionality of service crops in mediterranean vineyards using a functional trait approach - Léo Garcia; Aurélie Metay; Gaëlle Damour (PLoS ONE, 2026)
Vineyard soils face various agronomic issues such as poor organic carbon levels, erosion, fertility losses, and numerous studies have highlighted the ability of service crops to address these issues. Because biodiversity enhances the multifunctionality of managed ecosystems, service crop mixtures that increase functional diversity represent a promising option to improve vineyard sustainability. Plant functional traits play a crucial role in understanding ecosystem functions, serving as drivers for ecosystem processes and influencing ecosystem services, but the relationship between plant functional traits and ecosystem services is also complex. This study aimed to identify the links between the functional structure of the service crops associated with grapevines, the function they deliver and ecosystem function multifunctionality (EFM), in a Mediterranean vineyard. Thirteen different monocultures of service crop species were sown in the inter-rows of plots of 30 m length that covered one row and the two adjacent inter-rows, at random locations. We then studied 38 plant communities each composed of one of the sown service crop and the spontaneous vegetation that developed with it. At vine budburst, we simultaneously measured five indicators of ecosystem functions (runoff reduction, soil stabilization, soil mineral nitrogen supply for the vine, soil water supply for the vine, and community biomass production), along with 12 above- and below-ground functional markers of the community associated with these functions, in each plant community. Relationships between ecosystem functions and functional markers were analyzed by combining PCA, correlations and multiple linear regressions. We showed that traits upscaled at the community level (CWM) explained part of the targeted functions: significant correlations between traits and functions ranged from 0.33 to 0.6; the R 2 values of the linear regression models between functional indicators and the PCA axes derived from the traits ranged from 0.16 to 0.56. Additionally, we identified tradeoffs between functions, and observed that the biomass production was a major driver of soil-based ecosystem functions. In conclusion, functionally different communities provided different levels of functions and EFM. Designing service crops communities with complementary plant traits may be particularly relevant for increasing multifunctionality and agrosystem sustainability.